Arthroscopic anatomy of the equine cervical articular process joints. (3rd September 2013) - Pepe, M.; Angelone, M.; Gialletti, R.; Nannarone, S.; Beccati, F.
Summary Reason for performing study Although arthropathy of the cervical articular process joints (APJs) is common, descriptions of the arthroscopic technique of the cervical APJ have not been reported previously. Objectives To develop an arthroscopic approach to the APJ and to describe the arthroscopic anatomy of the APJ. Study design Descriptive cadaver study and clinical case report. Methods The regional anatomy was reviewed and the technique developed on fresh cadaver necks. A series of cadaveric APJ arthroscopies from C2–C3 to C6–C7 were performed to evaluate the procedure, which was then used in 3 clinical cases. A description of the procedure and the potential complications encountered were recorded. Results The equine APJ consists of cranioventral and caudodorsal recesses; a single entry point at one of these recesses enables almost complete evaluation of cartilage surfaces and the synovial membrane and its villi. Successful entry into both APJ recesses was achieved in 22 cadaveric APJs and 5 APJs in the 3 clinical cases operated upon. An instrument portal was created to assess the feasibility of surgical arthroscopy. Complications were minor, and dissection of the APJs following the arthroscopic exploration revealed that the cartilage and periarticular neurovascular structures were not damaged during the procedure. Conclusions This study shows that arthroscopic examination of the APJs of equine cervical vertebra is feasible and can be performed in mature horses. Arthroscopy of the APJs may provide additional diagnostic information compared to conventional diagnostic techniques.